Black Soldier Fly (Hermetia illucens) Maggot Flour as Concentrate Substitution on Broiler Chickens Feed Consumption, Body Weight Gain and Feed Conversion Ratio - Magdalena Eki Pertiwi; Sri Hidanah; Nove Hidajati; Mirni Lamid; Widya Paramita Lokapirnasari; Sunaryo Hadi Warsito (Universitas Airlangga, 2023)
This study aims to determine the effect of concentrate substitution with maggot Black Soldier Fly (Hermetia illucens) flour on feed consumption, body weight gain and feed conversion ratio of broiler chickens. This study was an experimental study with a completely randomized design (CRD) with 5 treatment and 4 replications. The material uses broiler chickens age four weeks as many as 20 tails, the feed used is concentrate from the PT. Charoen Pokphand Indonesia, maggot BSF flour, corn and bran. The feed treatment with the addition of maggot BSF flour consisted of P0 (feed without maggot BSF flour), P1 (2% addition of maggot BSF flour), P2 (4% addition of maggot BSF flour), P3 (6% addition of maggot BSF flour), and P4 (8% addition of maggot BSF flour). From the study results obtained the mean and standard deviation of feed consumption, body weight gain and feed conversion of broiler chickens. Analisys of Variance (ANOVA) showed that the subtitution of concentrate with maggot flour from black soldier flies had no significated effect (p>0.05) on the feed consumption, body weight gain and feed conversion ratio of broiler chickens.